A Photoacoustic‐Fluorescent Imaging Probe for Proteolytic Gingipains Expressed by Porphyromonas gingivalis. Issue 30 (13th June 2022) - Moore, Colman; Cheng, Yong; Tjokro, Natalia; Zhang, Brendan; Kerr, Matthew; Hayati, Mohammed; Chang, Kai Chiao Joe; Shah, Nisarg; Chen, Casey; Jokerst, Jesse V.
Abstract: Porphyromonas gingivalis is a keystone pathogen in periodontal disease. We herein report a dual‐modal fluorescent and photoacoustic imaging probe for the detection of gingipain proteases secreted by P. gingivalis . Upon proteolytic cleavage by Arg‐specific gingipain (RgpB), five‐fold photoacoustic enhancement and >100‐fold fluorescence activation was measured with detection limits of 1.1 nM RgpB and 5.0E4 CFU mL −1 bacteria in vitro. RgpB activity was imaged in porcine jaws with low‐nanomolar sensitivity. Diagnostic efficacy was evaluated in gingival crevicular fluid samples from subjects with and without periodontal disease, wherein activation was correlated to qPCR‐based detection of P. gingivalis (Pearson's r =0.71). Finally, photoacoustic imaging of RgpB‐cleaved probe was achieved in murine brains ex vivo, with relevance and potential utility for disease models of general infection by P. gingivalis, motivated by the recent biological link between gingipain and Alzheimer's disease. Abstract : Porphyromonas gingivalis is a keystone bacteria in periodontal disease, and the gingipain proteases from P. gingivalis are a biomarker of infection. A small‐molecule contrast agent that produces fluorescence and photoacoustic signals in the presence of gingipains is reported. This probe was used with animal models and was further validated with human samples of gingival crevicular fluid.